Behaviors of coking and stable radicals of a heavy oil during thermal reaction in sealed capillaries. (15th November 2017) - Chen, Zezhou; Yan, Yuxin; Zhang, Xurui; Shi, Xinge; shi, Lei; Liu, Qingya; Liu, Zhenyu; Xu, Teng
Highlights: Reaction of a heavy oil is studied in sealed capillaries at 250–500 °C. Mass and radical concentration of two types of cokes are quantified. The temperatures of these cokes' formation and transformation are reported. These cokes are characterized by radical concentration and line width of ESR. Activation energy of radical concentration is compared with that of coke formation. Abstract: This work studies thermal reaction of a heavy oil at temperatures of 250–500 °C in sealed capillaries. The samples are extracted by chlorobenzene and toluene, and the insoluble matters are quantified in mass and in radical concentration. It is found that the chlorobenzene insolubles (CI) forms at temperatures of and higher than 440 °C while the toluene insolubles (TI) forms at temperatures higher than 350 °C. Both of these insoluble matters increase with time and temperature, and approach to similar asymptotic values. The CI formation can be fitted with a combination of the second-order and autocatalytic kinetics while the TI formation can be fitted with the second-order kinetics. Both CI and TI contain stable radicals measurable by electron spin resonance (ESR), and the radical concentration in CI is higher than that in TI. The kinetics of stable radical concentration in CI and TI are different from that in mass, except that of TI at a low temperature range (350–440 °C). The changes in ESR line width of CI and TI are also studied. The above data are also discussed in terms of hard coke (CI insoluble matters) and soft coke (the difference between TI and CI), and in activation energy.